Video-assisted Cooperative Physical Learning Model to Improve Student Learning Achievement - Yudaparmita, Gusti Ngurah Arya; Parwata, I Gusti Lanang Agung; Sudiana, I Ketut; Dharmadi, Made Agus (LPPM Undiksha, 2024)
The lecture method, which focuses too much on theoretical knowledge, fails to provide opportunities for students to practice healthy living and safety skills, which should be the core of health education. This leads to the diversity of student learning achievements. This study aims to analyze the effect of the Collaborative Teamwork Learning-based physical education learning model assisted by learning videos on student learning achievement. The subjects involved in this study amounted to 40 students. This type of research is experimental research, with the research design used as a quasi-experiment called nonequivalent posttest-only control group design. The data collection methods used include observation, questionnaires, and tests, while the instrument used is a learning achievement test. After the data is collected, it is analyzed using the data analysis method used in this research including descriptive analysis and inferential statistical analysis. The results showed that the physical education learning model based on Collaborative Teamwork Learning with the help of learning videos proved to influence learning achievement. Therefore, it can be concluded that this model can be one of the solutions in the physical education learning process. The development of this learning model is expected to positively contribute to improving student learning achievement, understanding, and leadership skills in physical education courses. The Collaborative Teamwork Learning-based physical education learning model with the help of learning videos is one alternative that can be used to increase the effectiveness of physical education learning.